137. Comparison of genotypic resistance pattern between Enterococcus faecium and Enterococcus faecalis to better understand the occurrence of mutations. (15th December 2022) - Padakanti, Sowmya; Badhiwala, Vismay; Hwang, Munok; Choi, Hosoon; Chatterjee, Piyali; Dhar, Sorabh; Kaye, Keith S; Jinadatha, Chetan
Abstract: Background: Enterococcus is one of the major causes of nosocomial infections many with vancomycin resistance. About 50, 000 infections are reported per year due to vancomycin-resistant Enterococci . Understanding the genotypic mutations can help recognize the potential burden for antibiotic resistance that exists in a population. In this study, using whole genome sequencing (WGS) we aim to analyze the prevalence of genetic resistance markers for commonly used antibiotics for Enterococcal treatment. Methods: Whole genome sequencing was performed using the NextSeq (Illumina Inc., CA) on 60 isolates of E. faecium and 29 isolates of E. faecalis . The isolates were obtained from two different Detroit area hospitals from 2017-2019. The data from WGS was analyzed using EPISEQ CS TM (BIOMÉRIEUX, Marcy l 'Etoile, France) bioinformatic database to obtain specific resistance genes which would correspond to commonly used antibiotics for treatment of Enterococcal infections. Results: Among the 89 Enterococcus faecium and Enterococcus faecalis investigated, we identified a total of 33 unique resistance genes across 18 classes of antibiotics (Table 1). We detected genetic mutations efmA, pbp5, tet(L), liar, liaS unique to E. faecium and only emeA unique to E. faecalis . E. faecium and E. faecalis share 14 similar resistance genes. E. faecium and E. faecalis had 12 and 7 unique resistance genes, respectively but are of same drug classes. The most common antibiotic classes include aminoglycosides, tetracyclines, quinolones, beta-lactams, glycopeptides, macrolides, and pyrimidine analogs. Table 1: Enterococcus faecium and E. faecalis genetic mutations and drug class resistance Conclusion: Enterococcus faecium had a greater number of resistance genes with glycopeptide, aminoglycoside, and beta lactam resistance when compared to Enterococcus faecalis . Whereas Enterococcus faecalis had more resistance genes associated with macrolides, tetracyclines, pyrimidine analogs, and Bactrim. In general, both appear to have many genes that encode for resistance to major classes of antibiotics which are used for treatment of Enterococcal infections. Further comparison with phenotypic susceptibility testing data would help better understand the practical implications of our resistance gene testing. Disclosures: Piyali Chatterjee, PhD, AHRQ Grant # 1R03HS027667-01: Grant/Research Support|AHRQ Grant # 1R03HS027667-01: Central Texas Veterans Health Care System Keith S. Kaye, MD, MPH, Allecra: Advisor/Consultant|GlaxoSmithKline plc.: Receiving symposia honoraria|GlaxoSmithKline plc.: GlaxoSmithKline plc.-sponsored study 212502|Merck: Advisor/Consultant|qpex: Advisor/Consultant|Shionogi: Grant/Research Support|Spero: Advisor/Consultant Chetan Jinadatha, MD, MPH, AHRQ R01 Grant-5R01HS025598: Grant/Research Support|EOS Surfaces: Copper Coupons and materials for testing.